microRNA-625 inhibits tumorigenicity by suppressing proliferation, migration and invasion in malignant melanoma - Fang, Wei (Oncotarget, 2017)
Dysregulated microRNA (miR)-625 expression has been observed in several kinds of cancer. MicroRNAs are important factors in the development and progression of malignant melanoma, though the clinical significance and function of miR-625 in human malignant melanoma remain unclear. Levels of miR-625 expression were therefore determined in 36 pairs of malignant melanoma and adjacent non-tumor tissue using qPCR. The effects of miR-625 dysregulation on malignant melanoma cell proliferation, wound healing, migration and invasion in vitro and tumorigenicity in vivo were investigated using CCK-8, transwell assays, and a nude mouse subcutaneous tumor model. Bioinformatics analysis and luciferase reporter system were used to predict and confirm the target gene of miR-625. miR-625 levels were frequently decreased in malignant melanoma. Ectopic expression of miR-625 suppressed proliferation, wound healing, migration, and tumorgenicity in malignant melanoma. Moreover, miR-625 acted, at least in part, by suppressing potential target SOX2. These results show that miR-625 is a tumor suppressor that inhibits the development and progression of malignant melanoma, which suggests miR-625 is potentially a new diagnostic marker and therapeutic target of malignant melanoma.